(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The purpose of this article is to analyze the legal nature of the legitimacy of associations within the scope of the jurisprudence of the Supreme Federal Court, notably for the relevance of the theme regarding the defense of diffuse interests, collective rights and homogeneous individual rights. In order to achieve this objective, a two-stage research is broken down, namely: a historical analysis of the concepts, foundations and characteristics inherent in the collective process and the legal nature of the rules according to the doctrines and jurisprudence of the procedures and their implications. Through an inductive method of research, it was intended to elaborate a study that contemplated the appreciation of the cases judged by the Supreme Federal Court that dealt with the theme, to determine the legal nature of the legitimacy and the subjective and objective beacons, besides the effects. resulting from it, as regards collective protection by the associations.